Characteristics and Potential Production of Frozen Semen of Pasundan Bull - Santoso Santoso; Herdis Herdis; R. I. Arifiantini; A. Gunawan; C. Sumantri (Tropical Animal Science Journal, 2021)
Pasundan cattle are one of the Indonesian domestic resources of animal-genetic materials that need to be developed and conserved. The aims of this study were to evaluate the characteristics of sperm and the potential production of frozen semen of Pasundan bulls. Ten Pasundan bulls were divided into two groups based on their fresh sperm motilities. Pasundan bulls were grouped based on their sperm motilities into group A (70-79%) and group B (80-89%). Secondary data were collected and confirmed with the primary data. The semen volume, pH, color, consistency, mass movement, sperm concentration, motility, viability, membrane integrity, abnormality, and DNA integrity of fresh semen were evaluated. The semen was then diluted, frozen, and stored at -196°C. The results showed that the pH of the fresh semen in group B was lower (p<0.05) than group A. Sperm concentration per ejaculate showed no difference with a range of 4312.36x106 to 6303.52x106. The viability and DNA integrity of fresh semen were not different between group A (84.41±0.99%; 91.19±0.79%) and group B (86.35±2.16%; 92.58±0.35%). DNA integrity of frozen semen of group B (89.81±1.18%) was higher (p<0.05) than that of group A (86.83±0.60%). The sperm motility of frozen semen of group A (<40%) was lower compared to SNI number 4869-1:2017. The frozen semen production of Pasundan bulls was between 144.18 to 191.29 straws/ejaculate. In conclusion, only bulls from fresh-semen sperm motility 80%-89% (group B) are eligible to be used as a semen source for artificial insemination.